A Case of Sphenoid Sinusitis With Epidural Abscess due to Fungal Infection and Mixed Infection With Eikenella corrodens and Aggregatibacter segnis - Momotaro Harano; Shiori Tanaka; Kohei Inomata; Shoji Naito; Hidenori Yokoi (Case Reports in Otolaryngology)
We report a case of sphenoiditis with an epidural abscess due to a fungal infection and a mixed infection with Eikenella corrodens and Aggregatibacter segnis and its clinical course, including a literature review. The patient was a 60-year-old woman who visited the emergency department of our hospital with complaints of a sudden right-sided headache that had persisted for 5 days and vomiting for 1 day. She was admitted to the hospital for an examination. Blood test results indicated a strong inflammatory reaction, and a blood culture revealed Gram-negative bacilli. Based on computed tomography and magnetic resonance imaging findings, right sphenoid sinus mycosis and a right-sided epidural hematoma were suspected, and therefore, endoscopic sinus surgery was performed. Thinning and pulsation of the right lateral wall of the sphenoid sinus were noted intraoperatively. The patient also had bacteremia, and the epidural hematoma was considered to be an abscess. The patient’s symptoms improved postoperatively. Thus, she was discharged 20 days following the surgery after continuous administration of meropenem for the right-sided epidural abscess. Although cases of epidural abscesses due to infection of the sphenoid sinus are rare, in patients with severe headaches, the presence or absence of intracranial spread at an early stage must be considered to accurately diagnose and treat the pathology.